Method for producing sintered bricks by using bauxite dressing tailings as well as product and application thereof
By mixing bauxite tailings, fly ash and expanded perlite, aged and roasted, and making sintered bricks, the problems of low utilization rate of bauxite tailings resource and complex process are solved, and efficient utilization and performance improvement are achieved.
Patent Information
- Application Number
- CN202411748929.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-02
AI Technical Summary
In the prior art, the resource utilization rate of bauxite tailings is low, the process is complex, and the compressive strength and application scenarios of the steamed-grown bricks and non-autopressed aerated concrete are limited, resulting in waste of resources and environmental pollution.
By mixing 50-70 parts of bauxite tailings, 30-40 parts of fly ash, and 0-10 parts of expanded perlite, aged, wet bricks are prepared, dried and calcined, and sintered bricks are obtained. This method simplifies the process, reduces the difficulty of sintering, and improves product strength and insulation properties.
It realizes efficient utilization of bauxite tailings, simplifies the process flow, reduces production costs, improves the mechanical properties and insulation properties of sintered bricks, and is suitable for construction.
Smart Images

Figure CN119751018A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of producing building materials by utilizing industrial solid waste, and in particular to a method for producing sintered bricks by utilizing bauxite tailings, and a product and application thereof. Background Art
[0002] Bauxite resources are mainly diaspore-type bauxite, which has the characteristics of high aluminum and high silicon. Most of them are medium- and low-grade bauxite with an aluminum-silicon ratio (ratio of aluminum oxide to silicon dioxide, the same below) less than 7. Improving the grade of bauxite by flotation desiliconization and then using the economic Bayer process to produce alumina has become an effective way to improve the utilization rate of medium- and low-grade bauxite resources. The tailings produced after bauxite beneficiation are generally discharged directly into the tailings dam by increasing the slurry concentration. This will bring the following problems: (1) A large amount of tailings are piled up in the tailings pond, polluting the surrounding environment; (2) The capital construction investment, management and maintenance costs of the tailings pond are high, and the potential safety threat problem is also quite prominent; (3) A large amount of useful minerals in the tailings are discarded and not effectively utilized, resulting in an extreme waste of resources. Therefore, the comprehensive utilization of bauxite tailings urgently needs to be solved.
[0003] For example, the Chinese invention patent with publication number CN108530015A discloses a steam-cured brick made from bauxite tailings and its preparation method. The steam-cured brick of the invention is prepared from bauxite tailings, fly ash, lime, desulfurized gypsum, admixtures and water as raw materials. The preparation steps are as follows: first, the bauxite tailings, fly ash, lime and desulfurized gypsum are evenly mixed, and then water and admixtures are added to continue stirring; then the evenly stirred slurry is poured into the mold and cured for 3-4 hours in a humid environment of 45-60 ℃; after cleaning the excess slurry above the mold, the mold is placed in a steam curing tank or steam curing room, steam-cured at 70-100 ℃ for 20-24 hours, and the mold is removed after natural cooling. The bauxite tailings, fly ash and desulfurized gypsum in the invention are all solid wastes, realizing waste resource utilization. However, its bauxite tailings need to be calcined at a temperature of 800°C. The purpose of calcining bauxite tailings is to increase the activity of the material. The silica in the uncalcined bauxite tailings cannot react with additives such as lime and gypsum under steam-curing conditions. The calcination process increases the processing flow, and the calcined bauxite tailings need to be further crushed into bauxite powder before they can be used for brick making. In addition, the raw material composition and process of steam-cured bricks are relatively complex, and the compressive strength of steam-cured bricks is generally not as good as that of sintered bricks. It has a narrow application range in application scenarios with high requirements for weathering resistance, frost resistance, and durability, which limits its use.
[0004] For another example, the Chinese invention patent with publication number CN108395178A provides a non-autoclaved aerated concrete containing bauxite tailings and a preparation method thereof. The non-autoclaved aerated concrete of the invention is prepared with bauxite tailings powder, fly ash, lime, gypsum, cement, water, aluminum paste, and admixtures as raw materials. The preparation method uses high temperature treatment of bauxite tailings to convert its inactive minerals into highly active alumina and silica, and then alumina and silica generate new products under non-autoclaved conditions and can exist stably to improve the specific strength of aerated concrete. The invention realizes the resource utilization of industrial solid waste and has far-reaching environmental significance and social benefits. Similarly, the bauxite tailings powder of the invention needs to be calcined at a temperature of 800 ° C, and the amount of bauxite tailings added in its formula is low, the treatment effect of bauxite beneficiation tailings per unit dosage is low, and the raw material composition and process are relatively complex.
[0005] In summary, a method for producing sintered bricks using bauxite beneficiation tailings is provided to solve the problems existing in the prior art, which has positive significance for expanding the comprehensive utilization of bauxite beneficiation tailings. Summary of the invention
[0006] In view of the above-mentioned defects of the prior art, in a first aspect of the present invention, a method for producing sintered bricks using bauxite tailings is provided, which has high utilization rate of bauxite tailings, convenient process and high production flexibility, and comprises the following steps: (1) In parts by weight, 50-70 parts of bauxite tailings, 30-40 parts of fly ash, and 0-10 parts of expanded perlite are mixed to obtain a mixture; the moisture content of the mixture is controlled within a certain range, and an aging treatment is performed to obtain an aged raw material; (2) making wet bricks from aged raw materials; (3) The wet bricks are dried to control their moisture content within a certain range to obtain dry bricks; (4) The dry bricks are fired and then naturally cooled to obtain sintered bricks.
[0007] Alumina is difficult to form glass phase and crystal phase with other components at 950-1050 ℃. Alumina can form mullite crystal phase with silicon oxide at above 1200 ℃. The main purpose of limiting the aluminum-silicon ratio is to limit the aluminum content. When the aluminum-silicon ratio is high, the aluminum content is high and the sintering temperature is high. Therefore, the present invention is suitable for controlling the aluminum-silicon ratio in the raw material within a certain range to reduce the difficulty of sintering, optimize the powdering of the brick surface, and improve the product strength.
[0008] Preferably, in step (1), the aluminum-silicon ratio of the bauxite tailings is less than 1.3; and the aluminum-silicon ratio of the fly ash is less than 0.7.
[0009] Preferably, in step (1), the moisture content of the mixture is controlled to be between 15% and 20%.
[0010] Aging is beneficial to promote the disintegration of raw material particles, loosening of mud balls, and homogenization of water. After an appropriate period of aging, the raw materials are more convenient to shape, showing good plasticity, easy shaping, fewer cracks, and low extrusion pressure. At the same time, the quality of the bricks is improved, such as smooth surface, good density, and not easy to crack, and the molding qualification rate is also improved accordingly.
[0011] Preferably, in step (1), the aging treatment lasts for 48-72 hours.
[0012] Preferably, in step (2), the aged raw material is extruded, formed and cut into green bricks of target shape.
[0013] Controlling the moisture content of dry bricks within an appropriate range helps optimize the quality of the finished product. If the moisture content is too high, the surface of the product may have defects such as fine network cracks, dumb bricks, and white spots. In addition, high moisture content is not conducive to the development of brick strength and is prone to deformation and tilting during the firing process.
[0014] Preferably, in step (3), the moisture content of the dry brick is less than 6%.
[0015] Preferably, in step (4), the calcination temperature is 950-1050°C and the holding time is 1-2 h.
[0016] The tunnel kiln is a modern continuous firing thermal equipment, which is built of refractory materials, thermal insulation materials and building materials, and is equipped with kiln cars and other vehicles inside, and its shape is similar to a tunnel. The working principle of the tunnel kiln is based on countercurrent operation. It is divided into three zones along the length of the kiln: preheating, firing and cooling. The product and the airflow move in opposite directions, and the preheating, firing and cooling processes of the product are completed in sequence in the three zones. The drying and roasting process of the sintered bricks of the present invention can be completed by a tunnel kiln commonly used in the field, without the need for specialized equipment, and has the advantages of wide applicability and automated production.
[0017] Preferably, in steps (3) and (4), the drying and roasting operations are carried out in a tunnel kiln.
[0018] In a second aspect of the present invention, there is provided a sintered brick having good mechanical properties and good thermal insulation properties, which is made by the preparation method of the first aspect of the present invention.
[0019] In the third aspect of the present invention, there is provided an application of the fired bricks according to the second aspect of the present invention, specifically using the fired bricks as building materials in construction.
[0020] Based on the above technical scheme, the design concept and principle of the present invention is to use simpler bauxite tailings, fly ash, and expanded perlite as raw materials for production, and to produce sintered bricks using a general brick material preparation process. The technical difficulty that the present invention needs to overcome is that the particles of bauxite tailings are very fine, and the particle size below -0.010mm can reach more than 50%. When high-doped bauxite tailings are used to make bricks, the drying shrinkage rate and firing shrinkage rate of the brick blank are both large, and the brick blank is prone to cracking if the drying and sintering processes are not well controlled. And when using bauxite tailings alone to make bricks, the viscosity of the brick blank is too large, and extrusion molding is difficult. The drying shrinkage and firing shrinkage are both relatively large. The brick blanks are stacked on the kiln car. During the drying and sintering process, due to the large shrinkage, they are prone to collapse.
[0021] Therefore, the present invention adds fly ash and expanded perlite to significantly reduce the drying shrinkage and sintering shrinkage of the brick blank, so that the brick blank is not easy to crack during the drying and sintering process. The addition of fly ash is mainly considered to increase the plasticity of the brick blank and reduce the drying shrinkage and sintering shrinkage of the brick blank. Fly ash contains a large amount of amorphous silicon dioxide, which can participate in the reaction to form stable compounds at a certain temperature. The reaction is slow in the initial stage. This delayed active reaction reduces the drastic volume change caused by rapid water loss, thereby reducing the shrinkage during the drying and sintering process. The fly ash particles have a glass microsphere structure, which fills microscopic pores in the mixture and contains more closed pores. The presence of pores reduces the density of the overall material, making the stress distribution generated by the evaporation of water during the drying process more uniform, thereby reducing the tendency of shrinkage and deformation. Expanded perlite is a powdered granular product formed after expansion under high temperature. In the production process of sintered bricks, the porosity of expanded perlite enables it to play a certain buffering role in the mixture, absorb part of the stress generated by thermal expansion and contraction, prevent large cracks and deformation inside the material, and further reduce the shrinkage. In addition, the porous structure of expanded perlite can improve the thermal insulation performance of the brick body, and its addition amount can be properly controlled to produce load-bearing thermal insulation bricks.
[0022] During the roasting process, SiO2, Fe2O3, K2O, CaO and other raw materials form glass phase at high temperature, filling between insoluble particles to optimize strength development. Fly ash and expanded perlite are formed at high temperature and contain a large amount of glass phase. At high temperature, the tailings of bauxite can react with fly ash and expanded perlite to form a new glass phase, optimizing the comprehensive performance of sintered bricks.
[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects: The present invention provides a method for producing sintered bricks by utilizing bauxite tailings. The method has simple raw material ratio, easy to control production process parameters, and significantly reduces the drying shrinkage and sintering shrinkage of brick blanks. Industrial solid waste bauxite tailings can be utilized on a large scale to realize automated production, save the construction and maintenance costs of bauxite tailings ponds, and generate certain economic benefits.
[0024] The invention provides a sintered brick having good mechanical properties and thermal insulation properties.
[0025] The invention provides an application of sintered bricks, which has good application prospects in building construction as a building material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a physical picture of the fired brick made in Example 2; Figure 2 This is a physical picture of the sintered brick made in Example 4. DETAILED DESCRIPTION
[0027] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0028] In the following embodiments: Bauxite tailings were taken from a domestic bauxite beneficiation plant. Their particle size distribution characteristics, chemical composition and mineral composition are shown in Table 1, Table 2 and Table 3 respectively.
[0029] Table 1: Particle size distribution characteristics of bauxite tailings
[0030] Table 2: Main chemical composition of bauxite tailings (wt.%)
[0031] Table 3: Phase analysis results of bauxite tailings (wt.%)
[0032] The fly ash was taken from a domestic coal-fired power plant and its chemical composition is shown in Table 4.
[0033] Table 4: Main chemical components of fly ash (wt.%)
[0034] Example 1 The method for producing sintered bricks by using bauxite tailings comprises the following steps: (1) By weight, 70 parts of bauxite tailings and 30 parts of fly ash are mixed to obtain a mixture; the moisture content of the mixture is controlled to be 15%-20%, and the mixture is aged in an aging bin for 48 hours to obtain an aged raw material; (2) Extruding and cutting the aged raw materials into green bricks of target shape; (3) Stacking the wet bricks on the tunnel kiln car for drying, so that the moisture content of the bricks after drying is reduced to below 6%, thereby obtaining dry bricks; (4) The dry bricks are sent to a tunnel kiln for baking. The baking temperature is controlled at 950°C and kept at this temperature for 1 hour. Then they are cooled naturally to obtain sintered bricks.
[0035] Example 2 The method for producing sintered bricks by using bauxite tailings comprises the following steps: (1) By weight, 60 parts of bauxite tailings and 40 parts of fly ash are mixed to obtain a mixture; the moisture content of the mixture is controlled to be 15%-20%, and the mixture is aged in an aging bin for 48 hours to obtain an aged raw material; (2) Extruding and cutting the aged raw materials into green bricks of target shape; (3) Stacking the wet bricks on the tunnel kiln car for drying, so that the moisture content of the bricks after drying is reduced to below 6%, thereby obtaining dry bricks; (4) The dry bricks are sent to the tunnel kiln for baking. The baking temperature is controlled at 1000℃ and kept at this temperature for 1 hour. Then they are cooled naturally to obtain sintered bricks. Figure 1 shown.
[0036] Example 3 The method for producing sintered bricks by using bauxite tailings comprises the following steps: (1) In parts by weight, 55 parts of bauxite tailings, 40 parts of fly ash, and 5 parts of expanded perlite are mixed to obtain a mixture; the moisture content of the mixture is controlled to be 15%-20%, and the mixture is aged in an aging bin for 48 hours to obtain an aged raw material; (2) Extruding and cutting the aged raw materials into green bricks of target shape; (3) Stacking the wet bricks on the tunnel kiln car for drying, so that the moisture content of the bricks after drying is reduced to below 6%, thereby obtaining dry bricks; (4) The dry bricks are sent to the tunnel kiln for baking. The baking temperature is controlled at 1050°C and kept at this temperature for 1 hour. Then they are cooled naturally to obtain sintered bricks.
[0037] Example 4 The method for producing sintered bricks by using bauxite tailings comprises the following steps: (1) By weight, 50 parts of bauxite tailings, 40 parts of fly ash, and 10 parts of expanded perlite are mixed to obtain a mixture; the moisture content of the mixture is controlled to be 15%-20%, and the mixture is aged in an aging bin for 72 hours to obtain an aged raw material; (2) Extruding and cutting the aged raw materials into green bricks of target shape; (3) Stacking the wet bricks on the tunnel kiln car for drying, so that the moisture content of the bricks after drying is reduced to below 6%, thereby obtaining dry bricks; (4) The dry bricks are sent to the tunnel kiln for baking. The baking temperature is controlled at 1000℃ and kept at this temperature for 2 hours. Then they are cooled naturally to obtain sintered bricks. Figure 2 shown.
[0038] Example 5 This example tests the comprehensive performance of the sintered bricks prepared in Examples 1-3 to study their effects in practical applications. The performance test indicators include compressive strength, density, water absorption, porosity, and thermal conductivity. The above tests are measured using the general standard test methods in this field. The performance test results of each sintered brick are shown in Table 5.
[0039] Table 5: Performance test results of fired bricks
[0040] In the test of thermal conductivity, compared with commercially available ordinary sintered bricks and bauxite tailings sintered bricks made at a sintering temperature of 1000°C without adding other ingredients (fly ash, expanded perlite), the thermal conductivity coefficients were measured to be 0.80 W / m·K and 0.83 W / m·K respectively. The thermal conductivity of the sintered brick in Example 4 can be reduced to 0.34 W / m·K, and the addition of fly ash and expanded perlite can significantly improve the thermal insulation performance of the bauxite tailings sintered brick. In addition, when only bauxite tailings (such as bauxite tailings sintered at a sintering temperature of 1000°C) are used, the compressive strength of the sintered brick is 35 MPa and the density is 2.02 g / cm 3 , water absorption rate 8.50%, porosity 20.08%), even if the method of the present invention is used to prepare sintered bricks, under the control of other optional parameters, there are still difficulties in extrusion molding of brick blanks, and cracking and deformation are likely to occur during the drying and sintering process due to large drying shrinkage and sintering shrinkage.
[0041] The present invention adds fly ash and expanded perlite to significantly reduce the drying shrinkage and sintering shrinkage of the brick blank, so that the brick blank is not easy to crack during the drying and sintering process. No cracking was observed in the sintered bricks made in the embodiments. The addition of fly ash increases the plasticity of the brick blank and reduces the drying shrinkage and sintering shrinkage of the brick blank. Fly ash contains a large amount of amorphous silicon dioxide, which can participate in the reaction to form stable compounds at a certain temperature. The reaction is slow in the initial stage. This delayed active reaction reduces the drastic volume change caused by rapid water loss, thereby reducing the shrinkage during the drying and sintering process. The fly ash particles have a glass microsphere structure, which fills microscopic pores in the mixture and contains a large number of closed pores. The presence of pores reduces the density of the overall material, making the stress generated by the evaporation of water during the drying process more evenly distributed, thereby reducing the tendency of shrinkage and deformation. Expanded perlite is a powdered granular product formed after expansion under high temperature. In the production process of sintered bricks, the porosity of expanded perlite enables it to play a certain buffering role in the mixture, absorbing part of the stress caused by thermal expansion and contraction, and preventing large cracks and deformation inside the material. Therefore, the sintered bricks of the present invention have overcome the defect of cracking as a whole.
[0042] The sintered bricks of the present invention also have excellent mechanical properties. During the roasting process, the components in the raw materials form a glass phase at high temperature, which is filled between the insoluble particles and optimizes the strength development. Fly ash and expanded perlite are themselves formed at high temperatures and contain a large amount of glass phase. At high temperatures, the components of bauxite tailings can react with fly ash and expanded perlite to form a new glass phase, thereby optimizing the comprehensive performance of sintered bricks. Example 2 showed the highest compressive strength in the test. After adding expanded perlite, its compressive strength decreased, but it still met the use requirements of general brick materials, and its thermal insulation performance was further improved, which can be used in application scenarios with higher thermal insulation requirements. Therefore, the present invention can adjust the raw material ratio as needed to produce a series of products with different strengths and different thermal insulation performances. The raw material ratio of the present invention is simple, the production process parameters are easy to control, and automated production can be achieved, with good industrialization prospects.
[0043] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for producing sintered bricks using bauxite tailings, characterized in that: The steps include: (1) In parts by weight, 50-70 parts of bauxite tailings, 30-40 parts of fly ash, and 0-10 parts of expanded perlite are mixed to obtain a mixture; the moisture content of the mixture is controlled within a certain range, and an aging treatment is performed to obtain an aged raw material; (2) making wet bricks from aged raw materials; (3) The wet bricks are dried to control their moisture content within a certain range to obtain dry bricks; (4) The dry bricks are fired and then naturally cooled to obtain sintered bricks.
2. The method for producing sintered bricks by using bauxite tailings according to claim 1, characterized in that: In the step (1), the aluminum-silicon ratio of the bauxite tailings is less than 1.3; and the aluminum-silicon ratio of the fly ash is less than 0.
7.
3. The method for producing sintered bricks by using bauxite tailings according to claim 1, characterized in that: In the step (1), the moisture content of the mixture is controlled to be between 15% and 20%.
4. The method for producing sintered bricks by utilizing bauxite tailings according to claim 1, characterized in that: In the step (1), the aging treatment lasts for 48-72 hours.
5. The method for producing sintered bricks by using bauxite tailings according to claim 1, characterized in that: In the step (2), the aged raw material is extruded, formed, and cut into green bricks to form wet bricks of target shape.
6. The method for producing sintered bricks by utilizing bauxite tailings according to claim 1, characterized in that: In the step (3), the moisture content of the dry brick is less than 6%.
7. The method for producing sintered bricks by utilizing bauxite tailings according to claim 1, characterized in that: In the step (4), the calcination temperature is 950-1050°C and the holding time is 1-2 h.
8. The method for producing sintered bricks by utilizing bauxite tailings according to claim 1, characterized in that: In the steps (3) and (4), the drying and roasting operations are carried out in a tunnel kiln.
9. A fired brick, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.
10. An application of the sintered brick according to claim 9, characterized in that: Fired bricks are used as building materials in building construction.
Citation Information
Patent Citations
Non-autoclaved aerated concrete containing bauxite tailings and preparation method thereof
CN108395178A
Steam-cured brick made of bauxite tailing and method for preparing steam-cured brick
CN108530015A
Method for preparing copy stone floor tile by mineral processing tailing of bauxite
CN101700672A
Geopolymer compositions
CN102325736A
Method for producing ganged brick by utilizing red mud and bauxite tailings
CN102515818A